Anti-hypercholesterol effects of gynura procumbens leaves aqueous extract on cholesterol-fed New Zealand white rabbits / Mohd Azrul Hisham Ismail - Ismail, Mohd Azrul Hisham (2016)
Atherosclerosis becomes premier cause of CVD related diseases and become major concern worldwide. Gynura procumbens or Sambung Nyawa contains active chemical constituents such as flavonoids, saponins, tannins, terpenoids and sterol glycosides which can be further highlighted on its possible therapeutic potential as phytomedicine alternatives towards prevention of degenerative diseases. The study was conducted to determine the effects of Gynura procumbens leaves aqueous extract in hypercholesterolemic-induced rabbits. Antioxidant capacities were measured via DPPH and FRAP assays, determination of total phenolic and total flavonoid content and also proximate analysis assessment. The extract showed antioxidant capacities, radical scavenging activities and contains nutritional composition. New Zealand White rabbits were induced with 0.5 % high cholesterol diets for 10 weeks. To study the hypercholesterol lowering effects of Gynura procumbens leaves aqueous extract, rabbits that induced with high cholesterol diets were given 100 mg/kg, 200 mg/kg and 400 mg/kg. Effects of Gynura procumbens extract on New Zealand White rabbits were studied by measuring its enzymatic antioxidants (SOD, GPX and CAT), lipid profiles (TC, TG, HDL and LDL), liver function test (ALP, ALT, AST and GGT), lipid peroxidation (MDA) and also histological changes (Sudan IV and H&E). After 10 week of treatment, significance increased of serum lipid profiles, liver function test and lipid peroxidation were observed in rabbits that were induced with high cholesterol diets. Lipid profiles, liver function test and lipid peroxidation levels of groups that have been given high cholesterol diets with supplementation of the extract show significance reduction compared to animals that have been only given high cholesterol diets. Enzymatic antioxidant activities of rabbits that have been given the extracts also show lower levels of SOD, GPX and CAT levels compared to HCD group. Histological study of the aorta shows that treatments with Gynura procumbens extract reduced the formation of the plaque in the aorta. The findings suggest that Gynura procumbens possesses potential antioxidant capacity and nutritional composition that may be beneficial factors in treating various types of diseases including cardiovascular diseases especially in reducing the risk of atherosclerosis.